Penggunaan Media Buku Pop Up Berbasis Budaya Untuk Meningkatkan Konsentrasi Belajar Siswa Pada Pembelejaran Daring (PTK Kelas 4 MIN 1 Kepahiang) - Dinda Miranda Putri; Alexon Alexon; Wurjinem Wurjinem (JURIDIKDAS, 2020)
This research aims to increase the student learning concentration of students in grade 4 to MIN 1 Kepahiang by applying media learning pop up book. This research is a classroom action research. The subjects of this study were 11 students consisting of 4 male students and 7 female students. The research procedure is in the form of a cycle. Each cycle consists of four stages including planning, implementing actions, observing and reflecting. The research instrument was in the form of observation sheet media learning pop up book and student learning concentration on online learning. The data analysis technique used is the observation sheet using the formula of the average score, the highest score, the lowest score, the difference in score and the range of values for each criterion. Thus the use of media learning pop up book can increase the learning concentration of grade 4 students of MIN 1 Kepahiang.Keywords: Media Learning Pop Up Book, Concentration.